2003
DOI: 10.1109/jsac.2003.816625
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-node initiated reservation (iir): a new signaling scheme for wavelength-routed networks

Abstract: Abstract-A problem of many distributed lightpath provisioning schemes is wavelength contention, which occurs when a connection request attempts to reserve a wavelength channel that is no longer available. This situation results from the lack of updated global link-state information at every node. In networks with highly dynamic traffic loads, wavelength contention may seriously degrade the network performance. To overcome this problem, we propose a new framework for distributed signaling and introduce a class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 14 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…The most recent studies dealing with the routing inaccuracy problem can be found in [12][13][14][15][16][17][18][19][20][21]. The contributions in [12][13][14][15] evaluate the impact on the blocking probability because of selecting lightpaths under inaccurate routing information.…”
Section: Rwa and Prediction Based Routingmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent studies dealing with the routing inaccuracy problem can be found in [12][13][14][15][16][17][18][19][20][21]. The contributions in [12][13][14][15] evaluate the impact on the blocking probability because of selecting lightpaths under inaccurate routing information.…”
Section: Rwa and Prediction Based Routingmentioning
confidence: 99%
“…The proposed analytical models and the presented simulation results show that the blocking ratio increases in a fixed topology when routing is done under inaccurate information. To counteract this blocking effect, new RWA algorithms, able to tolerate inaccurate network state information have been proposed in [16][17][18][19].…”
Section: Rwa and Prediction Based Routingmentioning
confidence: 99%
“…In [11,12], re-routing operations are activated once there is an outdated information-caused blocking. In [13], a scheme called intermediate-node initiated reservation is proposed for networks with sparse wavelength conversion. The main idea is to initialize the reservation operations on those nodes with wavelength conversion, before the connection request reaches the destination node, so that the chance of having outdated information is lowered.…”
mentioning
confidence: 99%
“…A closer look at these existing results shows that they are either for the case with only global information flooding where lightpath establishment decisions are made based on flooded information (e.g., [6,10,15,16]) or for the case with only local link-state information exchange (e.g., [7][8][9][11][12][13][14]). In this article, we study a different case where global information flooding and local information exchange co-exist in the same network that enables dynamic routing and wavelength assignment.…”
mentioning
confidence: 99%